2020
DOI: 10.1111/1759-7714.13289
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of topoisomerase‐II expression in patients with advanced non‐small cell lung cancer treated with amrubicin

Abstract: Background: Amrubicin chemotherapy is a treatment option for patients with non-small cell lung cancer (NSCLC) after third-line treatment in Japan. Although topoisomerase-II (Topo-II), a target of amrubicin, has been reported to be a prognostic or predictive marker for chemosensitivity and clinical outcomes in various types of malignancies, its effects in the Japanese population remain unknown. Methods: Data regarding 44 patients with advanced NSCLC treated with amrubicin between April 2004 and May 2014 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Additionally, we revealed that high Topo‐II expression is an independent prognosticator of LCNEC in large samples after surgical resection, consistent with various malignancies, including SCLC 19–22 . Xue et al have shown that Topo‐II inhibition inhibits NSCLC growth, invasion, and migration in vitro and tumor growth in vivo, which supports our results that high expression of Topo‐II is a prognostic factor after surgical resection 23 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, we revealed that high Topo‐II expression is an independent prognosticator of LCNEC in large samples after surgical resection, consistent with various malignancies, including SCLC 19–22 . Xue et al have shown that Topo‐II inhibition inhibits NSCLC growth, invasion, and migration in vitro and tumor growth in vivo, which supports our results that high expression of Topo‐II is a prognostic factor after surgical resection 23 .…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the effect of Topo‐II expression on anticancer drug therapy, several previous reports have shown that high Topo‐II expression may contribute to a superior response to Topo‐II inhibitors in breast cancer and NSCLC 13,24–26 . Reportedly, patients with SCLC expressing high Topo‐II present longer progression free survival with amrubicin therapy than those with SCLC expressing low Topo‐II 13 ; however, this is not significant in NSCLC 22 . Currently, there is no data on whether high Topo‐II expression is correlated with the efficacy of Topo‐II inhibitors in LCNEC.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that targeting topo2-α may provide a treatment strategy for patients with laryngeal cancer [ 37 ]. Low expression of topo2-α increased survival of patients with non-small cell lung cancer treated with amrubicin, a topo2-α inhibitor [ 38 ]. Thus, a decreased expression of topo2-α in the RJK-PAA and RJKEB-PAA cells may be indicative for enhanced sensitivity of these cells to drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, amrubicin has been approved for the treatment of patients with NSCLC and SCLC 172 . Furthermore, it is used as a therapy option in the chemotherapy of NSCLC after the 3rd-line treatment 170 . Phase II of clinical trials for the use of amrubicin plus pembrolizumab in the treatment of refractory SCLC (NCT03253068) is currently ongoing.…”
Section: Promising Active Epipodophyllotoxin Derivativesmentioning
confidence: 99%
“…Amrubicin (9-amino-anthracycline; SM-5887) is a synthetic anthracycline derivative with potent antitumor activity based on the hTop II inhibition ( Figure 9(c) ). Cytotoxic activity of amrubicin results from the stabilisation of DNA–hTop II cleavable complexes 169 , 170 . Moreover, amrubicinol, an active amrubicin metabolite, is 5–220 times more cytotoxic than the original compound 171 .…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%